How Culture Shapes Social Categorization and Inductive Reasoning:A Developmental Comparison between the United States and China. Issue 5 (20th October 2022) - Xu, Yian; Burns, Megan; Wen, Fangfang; Thor, Emily Dahlgaard; Zuo, Bin; Coley, John D.; Rhodes, Marjorie
ABSTRACT: Social categories allow us to make sense of the social world and generate predictions about novel encounters. Yet, how people use particular social categories varies by culture. The current study examined how social categorization varies across traditionally individualistic and collectivistic societies among young children and adults. Using a triad picture task, American and Chinese children and adults made categorization and inductive reasoning judgments based on categories perceived as biological (e.g., age and gender) or categories perceived as social (e.g., occupation). The developmental trajectory of social categorization varied by culture: American adults were more likely than American children to categorize based on biologically-relevant categories, whereas Chinese adults were more likely than Chinese children to do so based on socially-relevant categories. Chinese participants also relied on socially-relevant categories (occupation) to make predictions about physical properties more than American participants. The current findings suggest a broad cultural influence on the perceived meanings and structures of certain biologically- and socially-based categories.